Pentacene Appended to a TEMPO Stable Free Radical: The Effect of Magnetic Exchange Coupling on Photoexcited Pentacene - Chernick, Erin; Casillas, Ruben; Zirzlmeier, Johannes; Gardner, Daniel M.; Gruber, Marco; Kropp, Henning; Meyer, Karsten; Wasielewski, Michael R.; Guldi, Dirk Michael; Tykwinski, Rik (Journal of the American Chemical Society, 2015)
Understanding the fundamental spin dynamics of photoexcited pentacene derivatives is important in order to maximize their potential for optoelectronic applications. Herein, we report on the synthesis of two pentacene derivatives that are functionalized with the [(2,2,6,6-tetramethylpiperidin-1-yl)oxy] (TEMPO) stable free radical. The presence of TEMPO does not quench the pentacene singlet excited state, but does quench the photoexcited triplet excited state as a function of TEMPO-to-pentacene distance. Time-resolved electron paramagnetic resonance experiments confirm that triplet quenching is accompanied by electron spin polarization transfer from the pentacene excited state to the TEMPO doublet state in the weak coupling regime.
EAM Import::2019-03-08